Unveiling Thesis Pursuit: Self-Efficacy's Resilience against Academic Anxiety: Membeberkan Penelusuran Tesis: Ketahanan Diri Terhadap Kecemasan Akademik - Zain , Nurisma Putri; Rusyid Affandi, Ghozali (Universitas Muhammadiyah Sidoarjo, 2023)
This study addresses the pervasive issue of academic anxiety among undergraduates completing their theses, focusing on the Faculty of Psychology and Education at a prominent university. With a sample of 200 students, drawn using accidental sampling, the research explores the relationship between self-efficacy and academic anxiety. Self-efficacy was measured using a scale encompassing magnitude, strength, and generality, while academic anxiety was assessed through emotional, cognitive, and physical dimensions. Employing Rank Spearman correlation and SPSS 25.0, the analysis revealed a significant negative correlation (ρxy = -0.186, p < 0.05), underscoring the inverse connection between self-efficacy and academic anxiety during thesis work. These findings emphasize the potential of bolstering self-efficacy to mitigate academic anxiety, offering insights for educational institutions and practitioners to foster more confident and less anxious thesis pursuits. Highlights: Significant Relationship: The study uncovers a noteworthy negative relationship (ρxy = -0.186, p < 0.05) between self-efficacy and academic anxiety among students engaged in thesis work. Multi-Dimensional Assessment: Self-efficacy and academic anxiety were assessed through scales encompassing various dimensions, offering a comprehensive perspective on the interplay between these factors. Implications for Education: The findings underscore the potential of enhancing self-efficacy to alleviate academic anxiety during thesis pursuits, suggesting practical strategies for educational institutions to better support students in their research endeavors. Keywords: Academic anxiety, Self-efficacy, Thesis completion, Undergraduate students, Correlation.